(untitled) (Medico Legal Update, 2019)
Use of protocols in various nursing care activities do enhance the performance of nurses. This study was conducted with the aim of evaluating the effectiveness of the protocol on bio-psychosocial assessment of patients among the staff nurses in the general wards of a selected hospital. An evaluative approach was used to measure the effectiveness of the protocol on bio-psychosocial assessment of patients among the psychiatric nurses. The study was held among 60 staff nurses chosen by non-probability purposive sampling, who were working in the General ward of Father Muller Medical College hospital, Mangalore, India, on 60 admissions to the same general wards of the same hospital. The results revealed that post –interventional practice has increased from Day1 to Day5. The data demonstrated that there was a significant change in practice day by day. Participants have shown a great improvement in the bio-psychosocial assessment of the patients and 80% of the nurses accepted the procedure.